Effect of combustibles on the structural properties of LaFeO3 synthesized by auto-combustion - Hammouche, D.; Djani, F.; Omari, M. (Science des matériaux (Laboratoire LARHYSS), 2016)
Lanthanum ferrite, LaFeO 3 , is a perovskite type material with an  orthorhombic structure that was synthesized by auto-combustion of different fuels from where we have obtained the structure (in the presence of amine group no further calcination was needed). This perovskite structure was confirmed by : XRD, Infra-red spectroscopy (IR), UV-visible spectroscpy and laser particle size. Key Words : LaFeO 3 , perovskite, auto-combustion, XRD, IR, UV-visible and laser particle size.